Free products of finite groups acting on regular rooted trees - Gupta, C.K.; Gupta, N.D.; Oliynyk, A.S. (Algebra and Discrete Mathematics, 2007)
Let finite number of finite groups be given. Let n
be the largest order of their composition factors. We prove explicitly that the group of finite state automorphisms of rooted n-tree
contains subgroups isomorphic to the free product of given groups.